Appointing and role of sponsors according to Canon Law - Janczewski, Zbigniew (Prawo Kanoniczne, 2020)
In so far as possible, a person being baptised is to be assigned a sponsor. His role is very important. In the case of an adult baptism, the sponsor assists the person in christian initiation. In the case of an infant, the role is together with the parents or parent to present the child for baptism, and to help it to live a christian life befitting the baptised and faithfully to fulfil the duties inherent in baptism. This article is about sponsor’s appointing and role according to Canon Law. The first part shows the history of this problem. The next part of article is about appointing of sponsors, last part is about role of sponsors. Author of article puts forward a thesis, to order in case baptism of some children not appoint sponsors, and all his role to convey parents.